Five-component synthesis of dihydropyridines based on diketene. Issue 15 (13th April 2017) - Rezvanian, Atieh; Heravi, Majid M.; Shaabani, Zahra; Tajbakhsh, Mahmood
Abstract: A novel five-component strategy involving commercially available diketene, primary amines, malononitrile and various benzaldehydes for the synthesis of densely functionalized 1, 4-dihydropyridines in good yields was achieved. The reaction pathway involves a sequential ring-opening of diketene/enamine formation/Knoevenagel-condensation/Michael addition and 6- exo-tet cyclization, resulting in multiple bond-formation events including two C–C and three C–N bonds ultimately leading to the formation of the respective 1, 4-dihydropyridines. Graphical abstract: